Application-specific nuclear medical in vivo imaging devices. (12th May 2021) - Chaudhari, Abhijit J; Badawi, Ramsey D
Abstract: Nuclear medical imaging devices, such as those enabling photon emission imaging (gamma camera, single photon emission computed tomography, or positron emission imaging), that are typically used in today's clinics are optimized for assessing large portions of the human body, and are classified as whole-body imaging systems. These systems have known limitations for organ imaging, therefore application-specific devices have been designed, constructed and evaluated. These devices, given their compact nature and superior technical characteristics, such as their higher detection sensitivity and spatial resolution for organ imaging compared to whole-body imaging systems, have shown promise for niche applications. Several of these devices have further been integrated with complementary anatomical imaging devices. The objectives of this review article are to (1) provide an overview of such application-specific nuclear imaging devices that were developed over the past two decades (in the twenty-first century), with emphasis on brain, cardiac, breast, and prostate imaging; and (2) discuss the rationale, advantages and challenges associated with the translation of these devices for routine clinical imaging. Finally, a perspective on the future prospects for application-specific devices is provided, which is that sustained effort is required both to overcome design limitations which impact their utility (where these exist) and to collect the data required to define their clinical value.